A study on the relationship between internal factors and financial leverage on selected construction company in Malaysia / Nurul Atiqah Zharfa Zazali - Zazali, Nurul Atiqah Zharfa (Faculty of Business Management, 2017)
This study was conducted to explore on the relationship between internal factors and financial leverage on selected construction companies in Malaysia. Leverage is using the debt ratio as the dependent variables expressed by formula total liabilities divided by total assets. The independent variables are profitability, liquidity and tangibility. Data from 5 companies, Osiris website had been extracted for 7 years from 2009-2015 on a yearly basis. All data was analyzed using STATA 11 though Panel Data analysis. The finding reveals that liquidity is significant with leverage. Negative relationships exist between liquidity toward leverage while tangibility asset and profitability does not appear to be significantly related to the dependent variable